Not Just Being Lifted: Infants are Sensitive to Delay During a Pick-Up Routine - Fantasia, Valentina; Markova, Gabriela; Fasulo, Alessandra; Costall, Alan; Reddy, Vasudevi (Frontiers in Psychology, 2016)
In the present study we observed whether infants show online adjustments to the mother’s incipient action by looking at their sensitivity to changes as the pick-up unfolded. Twenty-three 3-month-old infants and their mothers were observed in the lab, where mothers were instructed (1) to pick up their infants as they usually did (normal pick-up), and then (2) to delay the pick-up for 6 seconds after placing their hands on the infants’ waist (delayed pick-up). In both Normal and Delayed conditions infant’s body tension, affective displays and gaze shifts were coded during three phases: Approach, Contact and Lift. Additionally, a measure of infants’ head support in terms of head lag at the beginning and end of Lift was computed. Results showed that in the normal pick-up infants tensed up their body during the Approach phase and increased their tension during contact, maintaining it through Lift; their head was also supported and in line with their body during Lift. When the pick-up was delayed, infants also tensed their body during Approach, yet this tension did not increase during the Contact phase and was significantly lower at Lift. Their head support was also lower in the Delayed condition and they shifted their gazes away from their mothers’ face more often. These results suggest that infants are sensitive to changes of the timing of the pick-up sequence, which in turn may have affected their contribution to the interaction.